Modeling radio wave propagation in tunnels with a vectorial parabolic equation. - Popov, A.V (IEEE Transactions on antennas and propagation)
To study radio wave propagation in tunnels, we present a vectorial parabolic equation (PE) taking into account the cross-section shape, wall impedances, slowly varying curvature, and torsion of the tunnel axis. For rectangular cross section, two polarizations are decoupled and two families of adiabatic modes can be found explicitly, giving a generalization of the known results for a uniform tunnel. In the general case, a boundary value problem arises to be solved by using finite-difference/finite-element (FD/FE) techniques. Numerical examples demonstrate the computational efficiency of the proposed method